TÍNH NHANH
B 1 x 2 +2 x3 +3x4+......+99x140
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(A=2x^3-9x^5+3x^5-3x^2+7x^2-12=-6x^5+2x^3+4x^2-12\)
b, \(B=2x^4+x^2+2x-2x^3-2x^2+x^2-2x+1=2x^4-2x^3+1\)
c, \(C=2x^2+x-x^3-2x^2+x^3-x+3=3\)
a) A(x) = 2x3 + 5 + x2 - 3x - 5x3 - 4
= 2x3 - 5x3 + x2 - 3x + 5 - 4
= -3x3 + x2 - 3x + 1
B(x) = -3x4 - x3 + 2x2 + 2x + x4 - 4 - x2
= -3x4 + x4 - x3 + 2x2 - x2 + 2x - 4
= -2x4 - x3 + x2 + 2x - 4
b)
H(x) = A(x) - B(x)
H(x) = (-3x3 + x2 - 3x + 1) - (-2x4 - x3 + x2 + 2x - 4)
= -3x3 + x2 - 3x + 1 + 2x4 + x3 - x2 - 2x + 4
= 2x4 - 3x3 + x3 + x2 - x2 - 3x - 2x + 1 + 4
= 2x4 - 2x3 -5x + 5
\(a,=y\left(y-2\right)\\ b,=3x\left(x^2-2x+1\right)=3x\left(x-1\right)^2\\ c,=\left(y-1\right)\left(27x^2+9x^3\right)=9x^2\left(x+3\right)\left(y-1\right)\\ d,=y\left(y^2-2y+1\right)=y\left(y-1\right)^2\\ e,=x\left(x^2+6x+9\right)=x\left(x+3\right)^2\\ f,=x\left(x^2-2xy+y^2\right)=x\left(x-y\right)^2\\ g,=\left(2-x\right)\left(x+1\right)\\ h,=\left(x-1\right)\left(3x-6\right)=3\left(x-1\right)\left(x-2\right)\)
a: =y(y-2)
b: \(=3x^2\left(x^2-2x+1\right)=3x^2\left(x-1\right)^2\)
d: \(=y\left(y^2-2y+1\right)=y\left(y-1\right)^2\)
\(a,N\left(x\right)=x^2+3x^4-2x-x^2+2x^3=3x^4+2x^3+\left(x^2-x^2\right)-2x\\ =3x^4+2x^3-2x\\ P\left(x\right)=-8+5x-6x^3-4x+6=-6x^3+\left(5x-4x\right)+\left(-8+6\right)\\ =-6x^3+x-2\)
Bậc của N(x) là 4
Bậc của P(x) là 3
\(b,P\left(x\right)+N\left(x\right)=3x^4+2x^3-2x-6x^3+x-2\\ =3x^4+\left(2x^3-6x^3\right)+\left(-2x+x\right)-2\\ =3x^4-4x^3-x-2\)
\(c,B\left(x\right)=-2x^2\left(x^3-2x+5x^2-1\right)\\ =\left(-2x^2\right).x^3+\left(-2x^2\right).\left(-2x\right)+\left(-2x^2\right).5x^2+\left(-2x^2\right).\left(-1\right)\\ =-2x^5+4x^3-10x^4+2x^2\\ =-2x^5-10x^4+4x^3+2x^2\)
a) \(P\left(x\right)=3x^3-x^2-2x^4+3+2x^3+x+3x^4-x^2-2x^4+3+2x^3+x+3x^4\)
\(=2x^4+7x^3-2x^2+2x+6\)
\(Q\left(x\right)=-x^4+x^2-4x^3-2+2x^2-x-x^3-x^4+x^2-4x^3-2+2x^2-x-x^3\)
\(=-2x^4-10x^3+6x^2-2x-4\)
b) \(P\left(x\right)+Q\left(x\right)=2x^4+7x^3-2x^2+2x+6-2x^4-10x^3+6x^2-2x-4\)
\(=-3x^3+4x^2+2\)